Web application to build on common phrasal verbs in students of tenth basic grade at colegio particular Eloy Velásquez Cevallos, La Libertad, province of Santa Elena, school year 2017-2018. - Tomalá Tomalá, Liseth Viviana (2018)
The present research work used technological educational methods which promote ICTs use, in order to improve the teaching-learning process. At the same time, it is focused in the development of English learners skills, considering the vocabulary knowledge as an important factor to reach such developments, phrasal verbs conform parts of key vocabulary that learners have to manage, since native English communication includes them daily, with the combination of these facts, it is propose a web application as a tool that motivates tenth grade students from Colegio Particular “Eloy Velásquez Cevallos” to learn phrasal verbs, by performing online activities such as: karaoke, cards reading, games and similar exercises; to advance in their comprehension abilities and even other skills, as a consequence students get stronger foreign language comprehension as well as fluency. Finally, this work contributed to maintain the motivation and also assists in the learning-acquisition level that English Ecuadorian framework entails.